Scaffolding Terhadap Kesalahan Peserta Didik dalam Menyelesaikan Soal Berpikir Kritis Matematis - Syahnur, Rezki Nanda (Departemen Matematika, 2023)
This research aims to describe what and how student’s made error, and how Scaffolding Treatment impact students in term of student’s error when solving mathematics problem related to critical thinking skills. This research was conducted using descriptive method and qualitative approaches. The subject of the research were thirty-four senior high school students. To collect data, mathematics critical thinking test were given and purposively selected six students as respondent of scaffolding based interview. The results show that: 1) most of the errors made are incomplete process when answering (PTL) that cause by the lack of ability to create explanation, and misinterpretation of problem or concept that cause by lack of interpretation and analysis ability. 2) Scaffolding are useful to help students find error, comprehend new understanding, and trigger students to think critically.Keywords—Mathematical Critical Thinking, Scaffolding, Student’s Error